2012
DOI: 10.1186/1471-2229-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of BAC-end sequence derived SSRs, and their incorporation into a new higher density genetic map for cultivated peanut (Arachis hypogaea L.)

Abstract: BackgroundCultivated peanut (Arachis hypogaea L.) is an important crop worldwide, valued for its edible oil and digestible protein. It has a very narrow genetic base that may well derive from a relatively recent single polyploidization event. Accordingly molecular markers have low levels of polymorphism and the number of polymorphic molecular markers available for cultivated peanut is still limiting.ResultsHere, we report a large set of BAC-end sequences (BES), use them for developing SSR (BES-SSR) markers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 59 publications
6
79
2
2
Order By: Relevance
“…BESs have been proven to be valuable sources of SSRs [48, 49]. In our study, a total of 3,846 SSRs were identified from the 2,698 sweetpotato BESs.…”
Section: Discussionmentioning
confidence: 90%
“…BESs have been proven to be valuable sources of SSRs [48, 49]. In our study, a total of 3,846 SSRs were identified from the 2,698 sweetpotato BESs.…”
Section: Discussionmentioning
confidence: 90%
“…In case of cultivated peanut, the first SSR-based genetic map was constructed using only 135 SSR markers, covering a total of 1,270.5 cM map distance which covers half of the peanut integrated consensus map29. In the past decade, thousands of SSR markers have been developed in peanut from complementary DNAs (cDNAs), SSR-enriched genomic DNA libraries, and BAC-ends25323334353637, which greatly accelerated the construction of genetic map and QTL analysis in peanut21232425272829383940. Since the polymorphism of SSRs in a specific population largely depended on the genetic diversity between the parents of an experimental population, several such efforts were required to make available large number of SSRs in the public domain for genetic and QTL mapping studies.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we constructed a high-density linkage map with a total of 1,219 loci with the map length of 2,038.75 cM, covering nearly 80% of peanut genetic map represented by the integrated peanut map29. More than 85% of the 1,219 loci segregated in the population at the expected ratio of 1:1, which was significantly more than that of other studies2325293940. The high proportion of mapped loci following Mendelian segregation has provided good quality and precise genetic map for conducting QTL analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated map was then constructed with 324 marker loci covering 1352 cM genetic distance (Qin et al, 2012). In addition to the SSRs mentioned above, Wang et al (2012) have also used 1152 SSRs mined from 36,314 BAC-end sequences (BES) and constructed a genetic map with a total of 318 markers covering 1674.4 cM in a single mapping population. For the creation of the highest density map of a single population of cultivated peanut to date, Shirasawa et al (2012b) reported the use of in silico analysis of DNA sequence data from the parental lines, which increased the efficiency of polymorphic marker development by more than three-fold.…”
Section: Recent Advancement In Genetic Linkage Mapsmentioning
confidence: 99%